2008
DOI: 10.1063/1.2895747
|View full text |Cite
|
Sign up to set email alerts
|

Density profiles of Ar adsorbed in slits of CO2: Spontaneous symmetry breaking revisited

Abstract: A recently reported symmetry breaking of density profiles of fluid argon confined by two parallel solid walls of carbon dioxide is studied. The calculations are performed in the framework of a nonlocal density functional theory. It is shown that the existence of such asymmetrical solutions is restricted to a special choice for the adsorption potential, where the attraction of the solid-fluid interaction is reduced by the introduction of a hard-wall repulsion. The behavior as a function of the slit's width is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The behavior for a slit of reduced width L * = L/σ ff = 15 was examined. These authors claimed that a spontaneous symmetry breaking occurs for temperatures below the critical value T sb = 106 K. In a recent paper [Szybisz & Sartarelli, 2008] we revisited the investigation of [Berim & Ruckenstein, 2007] finding that, indeed, their conclusion was based on calculations performed with a s-f potential which includes a hardwall repulsion located in such a way that the depth of the s-f potential, D, was diminished. In fact, when the original [Ebner & Saam, 1977] potential is used, the spontaneous symmetry breaking disappears, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…The behavior for a slit of reduced width L * = L/σ ff = 15 was examined. These authors claimed that a spontaneous symmetry breaking occurs for temperatures below the critical value T sb = 106 K. In a recent paper [Szybisz & Sartarelli, 2008] we revisited the investigation of [Berim & Ruckenstein, 2007] finding that, indeed, their conclusion was based on calculations performed with a s-f potential which includes a hardwall repulsion located in such a way that the depth of the s-f potential, D, was diminished. In fact, when the original [Ebner & Saam, 1977] potential is used, the spontaneous symmetry breaking disappears, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…12 They analyzed a slit of width L =15 f f and stated that SSB occurs for temperatures below a critical value T sb = 106 K. In a revisited study of this system reported in Ref. 13, we found that the conditions for the occurrence of SSB had been fulfilled in Ref. 11 because the well depth of the s-f attraction was diminished by the presence of an extra hard-wall repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Since such a behavior was carefully discussed in previous works, 5,8,13 here we shall restrict ourselves to briefly outline the main features. When the liquid is adsorbed symmetrically like in the case of profile 3 in Fig.…”
Section: A Symmetry Of Density Profilesmentioning
confidence: 99%
“…However, in practice, it is usual 7,8,35 to solve the adsorption problem by fixing n together with V and T, that is by applying the CE scheme, which is much easier to manage numerically than the GCE one. Notice that μ and n are conjugate Legendre variables.…”
Section: Canonical Ensemblementioning
confidence: 99%
“…In most of the studies, a Canonical Ensemble (CE) statistics was applied to examine filling of closed slits with classical gases. [6][7][8][9][10][11][12] Recently, Berim and Ruckenstein 13 have also investigated the occurrence of SSB for quantum 4 He confined in planar slits. Furthermore, this kind of asymmetric solutions were also found by Merkel and Löwen in open systems.…”
mentioning
confidence: 99%